Bible Narratives and Youth Religious Identity: An Italian Exploratory Study - Michele Caputo; Tommaso Rompianesi (Religions)
Our article analyzes data from a broader exploratory Italian study on youth imaginaries and the role of narratives in attributing meaning to the world. The research gathered responses from 872 young people (aged 18 to 23) through a digital questionnaire. The data were analyzed with quantitative methodology using descriptive statistics. Our research questions can be formulated as follows: What level of familiarity do respondents have with biblical narratives? What narrative themes and categories do they use to define those stories? In relation to these elements, what are the characteristics of the respondents’ subgroups that defined themselves as “Religious”, “Indifferent/Agnostic”, and “Atheist”? The questionnaire items analyzed in this article provide an account of the respondents’ familiarity with some biblical narratives and their characters (Abraham, Jacob, and Ruth), as well as their choices related to the stories’ narrative themes and categories. The results from our sample open the field for further investigations, particularly in contexts characterized by different religious backgrounds (e.g., Protestant contexts), which may offer more nuanced interpretations of the educational process in relation to religious identity.